Strategic planning with ulū al-albāb approach - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi; Yahya, Rohaziah (WAIM, 2020)
Strategic planning process is paper-based with conceptual and intellectual approach. The use of mind is inclined towards ulū al-albāb approach. This study argued that ulū al-albāb approach is powerful to provide precise, rigorous and vigorous human-mind way. This human-minded way allows for human to express humane factor. Every economic, social and non-political inclined entity requires ulū al-albāb approach in strategic planning to enable the entity to achieve goals with efficiency and effectiveness. This study is to investigate the influence of ulū al-albāb approach in the practices of strategic planning in small and medium enterprises. This research objective is meant to answer two main research questions, namely (a) What are ulū al-albāb approach in strategic planning of small and medium enterprises?, and (b) In what ways ulū al-albāb approach provides efficiency and effectiveness sense in strategic planning of small and medium enterprises? The study found the level of ulū al-albāb in strategic planning and business models.